User interface design for i-Learn portal using eye-tracker / Dianacamelia Anak Ramba - Ramba, Dianacamelia (2011)
E-learning is an innovation technology with the aim to provide a strategy to improve the quality of teaching and learning. The establishment of i-Learn Portal, is to improve the teaching and learning environments at UITM and to have better learning delivering through electronic device. The interface design of i-Learn Portal plays an important role to deliver the learning process to both learners and educators. Thus, this study aimed to identify the interface design issues of i-Learn Portal in order to improve the existing interface design. A usability testing is conducted to evaluate i-Learn Portal interface design by utilizing the "Eye-Tracking" method to track the user's eye movement. Getting the user experience on i-learn was used to obtain the level of user satisfaction when interact with i-learn interface design. The data analyze from usability testing and eye tracking method is use to propose recommendation for the identified interface design issues. The recommendation of interface design for i-learn Portal will help to promotes usable learning portal for UiTM students in order to have an attractive interface design and increase the number of students interest to frequently access to i learn portal. UiTM lecturers which use i-learn portal also more easily interact with their student with better quality of teaching and interactive learning process. To i-learn Portal developer, this research help to develop LMS which adapt with diversity of individual aspect. From the design issues discovered will be able to improve i-learn portal to be more attractive and increase user satisfaction in using it.